The Effect of Firm Characteristics on the Voluntary Disclosures of Intellectual Capital in Annual Report (Case Study on Banking Sector Companies Registered on The Indonesia Stock Exchange) - Yulindisti, Elga (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2020)
The aim of this research study is to know whether profitability have significant effect on intellectual capital disclosure. The methodology using quantitative approach and the data is used secondary data. This research are used 50 annual reports of banking sector companies registered on Indonesia Stock Exchange as samples. The independent variable is profitability measured using Return of Equity and dependent variable is intellectual capital disclosure measure by Intellectual Capital Disclosure Index. This research used is simple linier regression analysis and the data testing is conducted by using SPSS 25. The results shown the profitability which is one of firm characteristics has no significant effect on voluntary of intellectual capital disclosure. Â Keywords: profitability, Firm characteristics, intellectual capital, voluntary disclosureÂ REFERENCESBontis, N. (1998). Intellectual capital: an exploratory study that develops measures and models. Management Decision, 36(2), 63â€“76.Brooking, A. (1996). Intellectual Capital. Core Asset for the Third Millennium Enterprise (1st ed.). London: Thomson Learning.Bukh, P. N., Nielsen, C., Gormsen, P., & Mouritsen, J. (2005). Disclosure of information on intellectual capital in Danish IPO prospectuses. Accounting, Auditing & Accountability Journal, 18(6), 713â€“732.Eccles, R. G., & Mavrinac, S. C. (1995). Improving The Corporate Disclosure Process. Sloan Management Review, 36(4), 11â€“25.Edvinsson, L., & Malone, M. (1997). Intellectual Capital: Realizing Your Companyâ€™s True Value by Finding Its Hidden Brain-power. New York: Harper Collins, NY.Guthrie, J., Petty, R., Ferrier, F., & Wells, R. (1999). There is no Accounting for Intellectual Capital in Australiaâ€¯: A review of annual reporting practices and the internal measurement of Intangibles 1 Macquarie Graduate School of Management Fran Ferrier Knowledge Management Solutions International , Sydney. In OECD Symposium on Measuring and Reporting of Intellectual Capital.Leslie. A, W., & Weatherly, L. A. (2003). The value of people: The challenges and opportunities of human capital measurement and reporting. SHRM Research Quaterly, 1â€“10.Meek, G. K., Roberts, C. B., & Gray, S. J. (1995). Factor Influencing Voluntary Annual Report Disclosures By U.S., U.K. And Continental European Multinational Corporations. Journal of International Business Studies, 26, 555â€“572.Petty, R., & Guthrie, J. (2000). Intellectual capital literature review and management. 1(2), 155â€“176.Purnomosidhi, B. (2005). Analisis Empiris Terhadap Determinan Praktik Pengungkapan Modal Intelektual Pada Perusahaan Publik BEJ. Journal TEMA, 6(2), 111â€“149.Roos, J., Roos, G., Dragonetti, N., & L, E. (1997). Intellectual Capital: Navigating in the New Business Landscape. New York: New York University Press, NY.Soon Yau, F., Sin Chun, L., & Balaraman, R. (2009). Intellectual Capital Reporting and Corporate Characteristics of Publicâ€Listed Companies in Malaysia. Journal of Financial Reporting and Accounting, 7(1), 17â€“35.Steward, T. (1997). Intellectual Capital: The New Wealth of Organizations. NewYork: Doubleday/Currency.Suhardjanto, D., & Wardhani, M. (2010). Praktik Intellectual Capital Disclosure Perusahaan Yang Terdaftar di Bursa Efek Indonesia. Jurnal Akuntansi Dan Auditing Indonesia, 14(1), 71â€“85.Sullivan, P. H., Patrick, J., & Sr, H. S. (2000). Valuing intangibles companies An intellectual capital approach. Journal of Intellectual Capital, 1(4), 328â€“340.Sveiby, K. (1997). The Intangible Assets Monitor. Journal of Human Resource Costing & Accounting, 2(1), 73â€“97.Ulum, I. (2015). Peran Pengungkapan Modal Intelektual dan Profitabilitas dalam Hubungan antara Kinerja Modal Intelektual dengan Kapitalisasi Pasar. Semarang: Universitas Diponegoro.Bontis, N. (1998). Intellectual capital: an exploratory study that develops measures and models. Management Decision, 36(2), 63â€“76.Brooking, A. (1996). Intellectual Capital. Core Asset for the Third Millennium Enterprise (1st ed.). London: Thomson Learning.Bukh, P. N., Nielsen, C., Gormsen, P., & Mouritsen, J. (2005). Disclosure of information on intellectual capital in Danish IPO prospectuses. Accounting, Auditing & Accountability Journal, 18(6), 713â€“732.Eccles, R. G., & Mavrinac, S. C. (1995). Improving The Corporate Disclosure Process. Sloan Management Review, 36(4), 11â€“25.Edvinsson, L., & Malone, M. (1997). Intellectual Capital: Realizing Your Companyâ€™s True Value by Finding Its Hidden Brain-power. New York: Harper Collins, NY.Guthrie, J., Petty, R., Ferrier, F., & Wells, R. (1999). There is no Accounting for Intellectual Capital in Australiaâ€¯: A review of annual reporting practices and the internal measurement of Intangibles 1 Macquarie Graduate School of Management Fran Ferrier Knowledge Management Solutions International , Sydney. In OECD Symposium on Measuring and Reporting of Intellectual Capital.Leslie. A, W., & Weatherly, L. A. (2003). The value of people: The challenges and opportunities of human capital measurement and reporting. SHRM Research Quaterly, 1â€“10.Meek, G. K., Roberts, C. B., & Gray, S. J. (1995). Factor Influencing Voluntary Annual Report Disclosures By U.S., U.K. And Continental European Multinational Corporations. Journal of International Business Studies, 26, 555â€“572.Petty, R., & Guthrie, J. (2000). Intellectual capital literature review and management. 1(2), 155â€“176.Purnomosidhi, B. (2005). Analisis Empiris Terhadap Determinan Praktik Pengungkapan Modal Intelektual Pada Perusahaan Publik BEJ. Journal TEMA, 6(2), 111â€“149.Roos, J., Roos, G., Dragonetti, N., & L, E. (1997). Intellectual Capital: Navigating in the New Business Landscape. New York: New York University Press, NY.Soon Yau, F., Sin Chun, L., & Balaraman, R. (2009). Intellectual Capital Reporting and Corporate Characteristics of Publicâ€Listed Companies in Malaysia. Journal of Financial Reporting and Accounting, 7(1), 17â€“35.Steward, T. (1997). Intellectual Capital: The New Wealth of Organizations. NewYork: Doubleday/Currency.Suhardjanto, D., & Wardhani, M. (2010). Praktik Intellectual Capital Disclosure Perusahaan Yang Terdaftar di Bursa Efek Indonesia. Jurnal Akuntansi Dan Auditing Indonesia, 14(1), 71â€“85.Sullivan, P. H., Patrick, J., & Sr, H. S. (2000). Valuing intangibles companies An intellectual capital approach. Journal of Intellectual Capital, 1(4), 328â€“340.Sveiby, K. (1997). The Intangible Assets Monitor. Journal of Human Resource Costing & Accounting, 2(1), 73â€“97.Â